Effects of European Monetary Integration on Intra-EMU Foreign Direct Investment - Pantelis Pantelidis; Dimitrios Kyrkilis; Efthymios Nikolopoulos (SPOUDAI - Journal of Economics and Business, 2014)
The creation of the European Monetary Union (EMU) created the conditions for increased trade and economic growth for the member countries. The initial hypothesis regarding the impact of euro launch in terms of Foreign Direct Investment (FDI) inflows was that monetary integration will affect positively the FDI. The aim of this paper is to construct and test a model explaining the intra-EMU FDI position of various EMU countries on the basis of their location advantages during 1985 - 2011 period. The model consists of variables approximating location advantages as these are suggested by economic theory and empirical research like market size, labor cost, openness, technology, interest rate and introduction of the Euro. The model focuses on the impact of EMU on FDI inflows and indicates that the monetary union has no significant impact on FDI inflows across individual member countries. The European market integration degraded the motives for market seeking FDI. Individual markets are now easier to be served through the conventional trade networks, and import substituting FDI becomes a less attractive option for the expansion of firms in Europe.
Keywords: F15; F21; F23; 330; FDI; EMU; euro